PENGARUH PEMBELAJARAN BERBASIS MASALAH BERBANTU APLIKASI GEOGEBRA TERHADAP PEMAHAMAN KONSEP SISWA - Elvianti, Elsa; Safaria, Sri Anandari; Agus, Imaludin; Dedyerianto, Dedyerianto; Hadi, Amanda La (UIN Imam Bonjol Padang, 2023)
One of learning media which is using in Problem-based learning that can improve students' conceptual understanding ability is GeoGebra. This study aims to: 1) describe the students' understanding of the concepts of SMA Negeri 1 Oheo. 2) determine the effect of problem-based learning assisted by the GeoGebra application on students' conceptual understanding at SMAN 1 Oheo. This research is pre-experimental research. The sampling technique uses simple random sampling. Class XI MIA as a research class. The data collection technique consists of students' conceptual understanding tests seen from the indicators explaining, understanding and concluding, as well as teacher observation sheets. The results of this study indicate that: 1) Students' conceptual understanding at SMAN 1 Oheo is in the high category where indicators of students being able to explain abstract concepts into a model have a 100% presentation, indicators of students being able to recognize and understand the main idea of a communication have a presentation 91.30%, and the student's indicator of being able to conclude from something that is already known material has an achievement of 78.26. 2) There is an effect of problem-based learning assisted by the GeoGebra application on students' understanding of concepts at SMAN 1 Oheo